2021
DOI: 10.3390/ma14247804
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Temperature Fields in Railway Solid and Ventilated Brake Discs

Abstract: A new approach to numerical simulation using the finite element method (FEM) for the rotational motion of discs for railway vehicle disc brake systems was proposed. For this purpose, spatial models of transient heating due to the friction of such systems with solid and ventilated discs were developed. The performed calculations and the results obtained allowed justification of the possibility of simplifying the shape of the ventilated brake disc through elimination of ventilation channels. This contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…This cease of zigzagged behaviour is likely related to the delay of heat conduction along circumferential direction, as the disc thickness increased from the surface. This is in agreement with other studies who reported 5 mm depth [17]. Hence, the NAMHS provides the better chance to reveal spatial and temporal variation in temperature.…”
Section: The Effect Of Pad Groove In Circumferentialsupporting
confidence: 93%
See 1 more Smart Citation
“…This cease of zigzagged behaviour is likely related to the delay of heat conduction along circumferential direction, as the disc thickness increased from the surface. This is in agreement with other studies who reported 5 mm depth [17]. Hence, the NAMHS provides the better chance to reveal spatial and temporal variation in temperature.…”
Section: The Effect Of Pad Groove In Circumferentialsupporting
confidence: 93%
“…However, the model didn't consider the spatial variations in heat input. After four years, the same authors modelled moving heat source by rotating disc layer close to friction surface around fixed heat source [17]. Though the model contributed significant drop in computational time, it requires further improvement in accommodating further complexity of disc and pad geometry, including disc surface bolt holes and pad grooves.…”
Section: Introductionmentioning
confidence: 99%
“…Such finite elements generated the most accurate results without the need to use an extremely fine mesh in the area of high temperature gradients. An experience in the construction of a finite element grid was obtained from previously conducted simulations of heat generation in disc brakes [ 25 ] and tread brakes (wheel-rail) of railway vehicles [ 26 ]. It was found that the linear finite elements significantly falsify the calculations (over 20%) even at many times higher than the default mesh density.…”
Section: Heating With Subsequent Cooling Of the Clutch Elements (Seco...mentioning
confidence: 99%
“…So far, various 3D FE models of frictional heating in friction elements that account for their complicated geometry have been proposed and examined [ 11 , 12 , 13 , 14 , 15 ]. A comparative numerical analysis of temperature in the solid and ventilated railway brake discs is presented in the study [ 14 ]. During the development of the calculation models, the ventilated disc has been replaced by a solid disc with the same mass and outer dimensions.…”
Section: Introductionmentioning
confidence: 99%